The regulation of administratively approved general contracting clauses in Peru - Tamani Rafael, Carlos (2024)
The present article examines the regulation and application of administrative approval of general contract clauses in the Peruvian context, with a focus on the financial services and telecommunications sectors.It highlights and questions the importance of this approval for consumer protection. Furthermore, it discusses jurisprudential discrepancies regarding the challenge of these clauses.In summary, the article offers a detailed and critical view of the regulation of general contract clauses in Peru, highlighting key challenges and considerations in this legal field.